A gendered magnifying glass on COVID-19 - Lorenzo Salvati; Benedetta Biagioni; Emanuele Vivarelli; Paola Parronchi (Clinical and Molecular Allergy, 2020)
Abstract COVID-19 pandemia is affecting Countries worldwide with a gendered death excess as being a male represents, especially in the 50–69 years age group, an unfavourable factor. Females are constitutionally prone to defend themselves against pathogens with a stronger efficiency than males. As a fact, several genes involved into the regulation of the innate and adaptive immune response are strategically placed on the X-chromosome and, among them, pathogen-related receptors (PRRs), such as Toll-like receptor 7, suitable to recognize ssRNAs and trigger a gendered successful anti-viral fight. On the other hand, a more regulated IL-6 production and a more contained inflammation after the encounter of a pathogen supply score points in favour of the female sex in the view that an abnormal and exaggerated cytokine release does represent the hallmark of the deathful SARS-CoV-2 infection. The sex-prevalent expression of the attachment and permissive molecules ACE2 and TMPRSS2 further supports the concept of a male-oriented vulnerability. In this review, the possible role of biological and immunological sex differences into the higher morbidity and mortality of SARS-CoV-2 between females and males are discussed.